2019
DOI: 10.1002/acn3.756
|View full text |Cite
|
Sign up to set email alerts
|

Plasma α‐synuclein levels are increased in patients with obstructive sleep apnea syndrome

Abstract: Objective Obstructive sleep apnea syndrome ( OSAS ) is characterized by nocturnal intermittent hypoxemia and can increase the risk of Parkinson's disease. This study aimed to investigate the association between plasma α ‐synuclein levels and hypoxia in the patients with OSAS . Methods We recruited 42 OSAS patients and 46 controls with simple snoring matched for ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“… 156 There is evidence that OSAS due to chronic intermittent hypoxia contributes to the pathogenesis of PD increasing the alfa-synuclein levels. 157 Severe and prolonged hypoxia contributes to brain damage, but moderate hypoxia exerts a neuroprotective effect through HIF-1alfa activation in PD model 158 while low level of HIF-1alfa is associated with neuronal dopaminergic cell loss in the substantia nigra pars compacta (SNpc) and contributes to PD pathogenesis. 159 HIF1alfa pathway is proposed as a therapeutic target for PD.…”
Section: Literature and Research Methodsmentioning
confidence: 99%
“… 156 There is evidence that OSAS due to chronic intermittent hypoxia contributes to the pathogenesis of PD increasing the alfa-synuclein levels. 157 Severe and prolonged hypoxia contributes to brain damage, but moderate hypoxia exerts a neuroprotective effect through HIF-1alfa activation in PD model 158 while low level of HIF-1alfa is associated with neuronal dopaminergic cell loss in the substantia nigra pars compacta (SNpc) and contributes to PD pathogenesis. 159 HIF1alfa pathway is proposed as a therapeutic target for PD.…”
Section: Literature and Research Methodsmentioning
confidence: 99%
“…Acute hypoxia in the mouse brain has been shown to lead to α‐synuclein upregulation, 31 whereas hypoxia conditioning seems to stabilize α‐synuclein levels 31 . Accordingly, in OSA patients, who experience severe hypoxic episodes during their sleep, α‐synuclein levels are elevated as well 32 . Hypoxic insult‐related upregulation of α‐synuclein levels possibly also favors or increases its aggregation, 33 and cellular acidification in response to hypoxia may increase α‐synuclein – mitochondria interactions 23 .…”
Section: Could Enhancing the Adaptive Response To Hypoxia Be Beneficial In Pd?mentioning
confidence: 99%
“…The exact mechanisms at play are still not fully understood, but, similar to AD, OSA, although not causing the disorder, likely plays a role in promoting or enhancing PD-associated pre-clinical pathological processes. Concurrent with this, Sun et al (2019) (N = 88) reported that both OSA severity and hypoxia markers were associated with increased levels of plasma αsynuclein, a key protein involved in PD pathology, in healthy adults [48]. With the onset of PD, the relationship between OSA and PD becomes more complex.…”
Section: Sleep Apnoea and Parkinson's Diseasementioning
confidence: 93%